What matters most? Students' rankings of simulation components which contribute to clinical judgement - Kelly, Michelle; Hager, P.; Gallagher, R. (McGraw-Hill, 2014)
As the pedagogy of health care simulation matures, the level of guidance provided and types of simulation components included increasingly vary. To prepare students for professional practice, one university embedded Tanner’s model of clinical judgment within the nursing curricula and integrated simulations. There was interest in seeking students’ opinions of “what matters most” in the design and delivery of simulations, which may vary from the academic’s viewpoint. Senior undergraduate nursing students (N = 150) from three types of study programs rated 11 simulation components in relation to clinical judgment. The three student groups rated all components above 2.9 on a 5-point Likert scale, with some variation across groups for component rankings. The highest ranking components for applying clinical judgment were facilitated debriefing, postsimulation reflection, and guidance by the academic. The lowest ranked components were patient case notes and briefing and orientation to the simulation area. Age and previous nursing experience did not influence the study variables.